Ice Engineering, Number 22, November 1999. Ice Jams, Winter 1997-1998 - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER NH (1999)
The Ice Engineering Information Exchange Bulletin is published as one of the information exchange functions of the Corps of Engineers. It is primarily intended to be a forum whereby information on ice engineering work done or managed by Corps field offices can be disseminated to other Corps office, other U.S. Government agencies and the engineering community in general. This issue provides a brief summary of ice jam data for water year 1998 (1 October 1997 through 30 September 1998) using information collected in the CRREL Ice Jam Database. Rivers, streams and lakes in cold regions freeze during winter months. Ice jams may form during initial ice cover formation (freeze up jams) or when ice cover breaks up (breakup jams). Both freeze up and breakup jams cause backwater flooding and damage to low-lying areas and municipal structures. The original document contains color images.